Rekayasa Lalu Lintas Jalan Tirto Agung akibat Aktivitas Antar Jemput Sekolah Al Azhar menggunakan Program VISSIM (Indonesian Journal of Civil Engineering Study, 2025)
Traffic congestion in urban areas has been a major issue for years, considering that the transportation demand cycle does not always allow for resolving congestion through road capacity expansion. Congestion caused by daily activities, such as the Al Azhar school pickup and drop-off, results in vehicle queues on Tirto Agung Street in Banyumanik. Therefore, it is necessary to analyze and apply traffic engineering strategies to improve intersection performance. Performance analysis of the intersection was conducted using PKJI 2023, and existing intersection conditions were modeled using VISSIM (Student Version) software. Based on the analysis using PKJI 2023, the existing intersection showed a degree of saturation (DJ) of 0.62, capacity (C) of 2776.48 vehicles/hour, intersection delay (T) of 11.32 seconds/vehicle, and queue probability (Pa) of 16%-34%, with a level of service index (ITP) of C (Sufficient). According to the VISSIM (Student Version) analysis, with the addition of traffic signals, the results showed a vehicle delay (VehDelay) of 8.50 seconds/vehicle, a queue length (Qlen) of 11.91 meters, and a level of service (LOS) of B (Good). Therefore, the traffic engineering recommendation for the Tirto Agung, Estetika Raya, and Klentengsari intersections is to implement a signalized intersection with a cycle time of 49 seconds.
Keywords: Traffic; Road capacity; Intersection performance; Vehicle delay